Academia, Activism, and Imprisoned Intellectuals - James, Joy (Social justice, 2003)
Academia often prides itself on being a site in which love, rage, or their symbiotic relationship do not dare to assert themselves, to proclaim and set a standard for communication, community, intellectual inquiry, or ethical and political action. As academics and activists, authors share a desire for learning, for encounters that lead to greater ethical and political agency, a passion for freedom. Daily, more political resisters and prisoners emerge in opposition to the U.S. wars, mass detentions and deportations and diminished civil liberties.